FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KARET ALAM INDONESIA KE AMERIKA SERIKAT (SEBELUM DAN SESUDAH KRISIS MONETER) - Silaban, Kristin Merlina; Damayanti, Yusma; Fitri, Yanuar (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
This study aims to determine the factors that affect Indonesia's natural rubber exports to the United States (before and after the monetary crisis). The objects of this research are world rubber prices, Indonesian rupiah exchange rates, Indonesian natural rubber production, synthetic rubber prices and exports in the previous year period. The data used in this study are secondary data obtained from the official website. Data analysis uses regression analysis of the Error Correction Model (ECM) in the long run and short run. The results showed that the factors that significantly affected Indonesia's natural rubber exports to the United States in the long run before the monetary crisis were world rubber prices (X1), the Indonesian rupiah exchange rate (X3), and the volume of natural rubber exports of the previous period (X5). Factors that significantly affected Indonesia's natural rubber exports to the United States in the short term before the monetary crisis were world rubber prices (X1), synthetic rubber prices (X4), and the volume of exports of natural rubber in the previous period (X5). Factors that significantly affect Indonesia's natural rubber exports to the United States in the long term after the monetary crisis are world rubber prices (X1), Indonesian natural rubber production (X3), and synthetic rubber prices (X4). Factors that significantly affected Indonesia's natural rubber exports to the United States in the short term after the monetary crisis were world rubber prices (X1), synthetic rubber prices (X4), and export volumes of natural rubber in the previous period (X5).